Association of the opposite sexes of Dryinus niger Kieffer, with notes on males of the other Western Palaearctic species of the same genus (Hymenoptera, Dryinidae) - Ødegaard, Frode; Rakhshani, Ehsan; Olmi, Massimo (Zootaxa, 2023)
In Fennoscandia, only one species of Dryinus (Hymenoptera, Dryinidae) is known, D. niger Kieffer, 1904. The species is very sporadically collected in that region, and the association of its opposite sex is difficult by its rarity. The capture of a male in Norway allowed us to describe it and place it in the new key to the males of Western Palaearctic Dryinus.